Evaluasi Penerapan Digital Accounting dalam Pencatatan Transaksi melalui Jurnal Umum pada Penyusunan Laporan Keuangan UMKM Kedai Azha - Sahrul Ramdhan; Masyuri, Masyhuri; Masyuri, Masyuri (Journal of Economics, Management, and Accounting, 2026)
This study aims to evaluate the implementation of digital accounting in recording financial transactions through general journals in the preparation of financial statements at Kedai Azha MSME. The research was motivated by the increasing adoption of digital technology in accounting practices, which is expected to improve efficiency, accuracy, and timeliness of financial reporting. A qualitative descriptive approach was employed using primary data obtained through in-depth interviews and direct observations. Secondary data were collected from financial documents, transaction records, and digital accounting reports. The findings indicate that digital accounting contributes positively to transaction recording consistency, financial reporting accuracy, and real-time monitoring of business finances. The system also supports transparency, accountability, and managerial decision-making through more reliable financial information. However, implementation effectiveness remains constrained by limited digital literacy, insufficient accounting understanding, human resource limitations, and technological adaptation challenges. The study concludes that digital accounting has substantial potential to strengthen financial management quality and business competitiveness among MSMEs when supported by adequate user competence and continuous digital capability development.